160 Injectable Vitamin C Prior to Transit and Transit Duration Effects on Feedlot Performance, Inflammation, and Muscle Fatigue of Beef Steers. (7th May 2021) - Beenken, Aubree M; Deters, Erin L; Hansen, Stephanie L
Abstract: This study examined the effects of injectable vitamin C (VC) before transport and duration of transit on feedlot performance, inflammation, and muscle fatigue in cattle. One hundred thirty-one, Angus-cross steers (409 ± 4 kg) were stratified by bodyweight (BW) to a 2 × 2 factorial of intramuscular injection (INJ; 20 mL/steer): VC (250 mg sodium ascorbate/mL) or saline (SAL) and road transit duration (DUR): 18 (18; 1, 770 km) or 8 h (8; 727 km). On d 0, steers were weighed and received INJ of SAL or VC immediately before transport. Upon return (d 1), BW and blood were collected before steers returned to pens with GrowSafe bunks. Steers were weighed on d 0, 1, 7, 15, 30, 31, 54, and 55. Data were analyzed via ProcMixed of SAS (experimental unit = steer; 32–34 steers/treatment) with fixed effects of INJ, DUR, and the interaction. Blood was collected on d -5, 1, 2, and 3 (9 steers/treatment); blood parameters were analyzed as repeated measures. Average daily gain (ADG) and BW were greater on d 7 and 15 for SAL-18 compared to all other treatments (INJ × DUR, P < 0.01). Final BW, overall ADG, and gain:feed were greater for 18 than 8 (P < 0.01). Injection did not affect BW (P > 0.13) but VC decreased overall dry matter intake compared to SAL (P = 0.03). Steers transported for 18 h had greater serum lactate, haptoglobin, and non-esterified fatty acid concentrations on d 1 compared to steers transported for 8 h (DUR × DAY, P < 0.01). Day 1 plasma ascorbate concentrations were greater for VC and returned to baseline concentrations by d 2 (INJ × DAY, P < 0.01). In contrast to previous work, VC did not improve post-transit performance; however, longer transit duration increased indicators of muscle fatigue and inflammation.